1987
DOI: 10.1177/073428298700500105
|View full text |Cite
|
Sign up to set email alerts
|

The Viability of Scatter Analysis On the Wisc-r aNd the Sbis: Examining a Vestige

Abstract: The history of scatter analysis on the WISC-R and the SBIS is reviewed. Evidence is presented that indicates that the practice of scatter analysis has yielded little of significance. Even in its most benign form, scatter analysis has the potential for doing more harm than good. Scatter analysis on the WISC-R, the SBIS, and similar tests is argued to be an exhausted research area, with little hope offered that any subsequent research efforts will prove beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…Thus, cognitive profiling approaches have been criticized for questionable reliability leading to an inability to provide scientifically rigorous diagnoses [43][44][45][46]. Miciak et al (2014) [45] examined the utility of two common PSW methods, (a) the concordance/discordance method [38] and (b) the cross-battery assessment method [39].…”
Section: The Resilience Of Discrepancy Testingmentioning
confidence: 99%
“…Thus, cognitive profiling approaches have been criticized for questionable reliability leading to an inability to provide scientifically rigorous diagnoses [43][44][45][46]. Miciak et al (2014) [45] examined the utility of two common PSW methods, (a) the concordance/discordance method [38] and (b) the cross-battery assessment method [39].…”
Section: The Resilience Of Discrepancy Testingmentioning
confidence: 99%
“…Despite this diversity, research has increasingly led to the conclusion that subtest patterns are diagnostically ineffective (for reviews, see Kavale 8c Forness, 1984;Kramer, Henning-Stout, & Schellenberg, 1987;Reschly 8c Grimes, 1990;Sattler, 1988). A common element in this research is the methodology of contrasted groups.…”
mentioning
confidence: 98%
“…Results of other recent studies with adults have indicated that the WAIS-R profiles of braindamaged patients, nondisabled controls, and psychiatric patients (e.g., with affective disorder, schizophrenia, psychosis) (Piedmont, Sokolove, & Fleming, 1989;Ryan, Paolo, & Smith, 1992) have comparable amounts and types of intersubtest variability. In fact, the overall paucity of positive findings in this area has led many reviewers to caution clinicians against over-interpreting intersubtest variability in IQ test profiles (e.g., Kramer, Henning-Stout, Ullman, & Schnellenberg, 1987).…”
mentioning
confidence: 99%